Diagnostic Performance of CMR, SPECT, and PET Imaging for the Identification of Coronary Artery Disease: A Meta-Analysis - Xu, Jianfeng; Cai, Fei; Geng, Changran; Wang, Zheng; Tang, Xiaobin (Frontiers in Cardiovascular Medicine, 2021)
Background: Myocardial perfusion imaging modalities, such as cardiac magnetic resonance (CMR), single photon emission computed tomography (SPECT), and Positron emission tomography (PET), are well-established noninvasive diagnostic methods to detect hemodynamically significant CAD. The aim of this meta-analysis is to compare CMR, SPECT, and PET in the diagnosis of CAD, and to provide evidence for further research and clinical decision-making. Methods: PubMed, Web of Science, Embase, and Cochrane Library were searched. Studies used CMR, SPECT and/or PET for the diagnosis of CAD were included. Pooled sensitivity, specificity, positive likelihood ratio (+LR), negative likelihood ratio (-LR), diagnostic odds ratio (DOR), with their respective 95% confidence interval (CIs) and the area under the summary receiver operating characteristic (SROC) curve (AUC) were calculated. Results: A total of 203 articles were identified for inclusion in this meta-analysis. The pooled sensitivity of CMR, SPECT and PET was 0.86, 0.83 and 0.85, respectively. Their respective overall specificity were 0.83, 0.77 and 0.86. Results in subgroup analysis of the performance of SPECT with 201Tl showed the highest pooled sensitivity (0.85 [0.82, 0.88]) and specificity (0.80 [0.75, 0.83]). 99mTc-tetrofosmin had the lowest sensitivity (0.76 [0.67, 0.82]). In the subgroup analysis of PET tracers, results indicated that 13N had the lowest pooled sensitivity (0.83 [0.74, 0.89]) and the specificity was the highest (0.91 [0.81, 0.96]). Conclusion: Our meta-analysis indicates that CMR and PET present better diagnostic performance for the detection of CAD as compared with SPECT.